Integrated Islamic School Principal Conflict Management Patterns in Improving Generation Z Teacher Performance: Systematic literature - Muhammad Nurul Arif; Dewi Cahyani; Moh. Ali (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to synthesize empirical and conceptual evidence from the latest literature on conflict management patterns applied by Integrated Islamic School (SIT) principals in managing Generation Z teachers and analyze its relationship with improving teacher performance. This study analyzes education regulations, national journal articles, and related textbooks using a systematic literature review method. The findings reveal that a comprehensive analysis identifies and maps four dominant patterns of conflict management: (1) the Collaborative-Digital pattern, which combines deliberation with digital platforms, (2) Accommodative-Spiritual Pattern emphasizing value-based mentoring approaches, (3) Transformative-Generational Pattern utilizing conflict as a catalyst for organizational cultural change, and (4) Preventive-Cultural Pattern focusing on building a harmonious school system and climate. These four patterns consistently integrate fundamental Islamic values such as deliberation (consultation), wisdom (hikmah), brotherhood (ukhuwwah), and reconciliation (ishlah) with psychological approaches that are adaptive to the unique characteristics of Generation Z, such as a preference for digital communication, a need for autonomy, and expectations of work-life balance. Data synthesis shows a significant positive correlation between the application of these patterns and improvements in various performance indicators of Generation Z teachers, particularly in the aspects of digital pedagogical innovation, organizational commitment, job satisfaction, and teaching productivity. This study recommends three main directions: (1) Development and validation of the “Islamic Intergenerational Conflict Management Framework (IICMF)” model, (2) Capacity building for school principals through integrative digital and multigenerational leadership training, and (3) Formulation of supporting policies that facilitate inclusive and transformative human resource management in Islamic educational institutions. The implications of this research include theoretical contributions to enriching the literature on Islamic educational leadership and practical contributions in the form of operational guidelines for stakeholders.